Modelling fuel flexibility in fixed-bed biomass conversion with a low primary air ratio in an updraft configuration. (15th July 2021) - Anca-Couce, Andrés; Archan, Georg; Buchmayr, Markus; Essl, Michael; Hochenauer, Christoph; Scharler, Robert
Highlights: 1D model of fixed-bed biomass conversion with updraft configuration. Investigations of fuel flexibility in boilers with such a bed conversion system. Temperature profiles and producer gas compositions were accurately predicted. Fuel moisture content, up to 30% w.b., does not affect the char conversion zone. Temperatures on the grate can only be reduced with flue gas recirculation. Abstract: Fixed-bed biomass conversion with a low primary air ratio and a counter-current configuration has a high feedstock flexibility, as it resembles updraft gasification, and the potential to reduce emissions when integrated in biomass combustion systems. A 1D bed model was validated with experimental results from a biomass combustion boiler with such a bed conversion system, predicting with a good accuracy the temperatures in the reactor and producer gas composition. The model was applied for different cases to investigate the fuel flexibility of this combustion system, including the influence of moisture content and the maximum temperatures achieved in the bed. It was shown that with variations in fuel moisture content from 8 to 30% mass w.b. the producer gas composition, char reduction to CO or maximum temperatures at the grate were not affected due to the separation of the char conversion and pyrolysis/drying zones. Flue gas recirculation was the only possible measure with the tested configuration to reduce the maximum temperatures close to the grate, which is beneficial e.g. to avoid slagging with complicated fuels. A higher tar content was obtained than in conventional updraft gasifiers, which is attributed to the absence of tar condensation in the bed due to the limited height of the reactor and the integration in the combustion chamber. The presented model can support the development of such combustion technologies and is a relevant basis for detailed CFD simulations of the bed or gas phase conversion.